Combined Heterozygous Genetic Variations in Complement C2 and C8B: An Explanation for Multidimensional Immune Imbalance? - Marco Mannes; Rebecca Halbgebauer; Lisa Wohlgemuth; David Alexander Christian Messerer; Susa Savukoski; Anke Schultze; Bettina Berger; Christiane Leonie Knapp; Christoph Q. Schmidt; Daniel Fürst; Morten Hillmer; Reiner Siebert; et al. (Karger Publishers, 2023)
The complement system plays a crucial role in host defense, homeostasis, and tissue regeneration and bridges the innate and the adaptive immune systems. Although the genetic variants in complement C2 (c.839_849+17del; p.(Met280Asnfs*5)) and C8B (c.1625C>T; p.(Thr542Ile)) are known individually, here, we report on a patient carrying their combination in a heterozygous form. The patient presented with a reduced general condition and suffers from a wide variety of autoimmune diseases. While no autoimmune disease-specific autoantibodies could be detected, genetic analysis revealed abnormalities in the two complement genes C2 and C8B. Therefore, we performed a comprehensive investigation of the innate immune system on a cellular and humoral level to define the functional consequences. We found slightly impaired functionality of neutrophils and monocytes regarding phagocytosis and reactive oxygen species generation and a diminished expression of the C5aR1. An extensive complement analysis revealed a declined activation potential for the alternative and classical pathway. Reconstitution with purified C2 and C8 into patient serum failed to normalize the dysfunction, whereas the addition of C3 improved the hemolytic activity. In clinical transfer, in vitro supplementation of the patient's plasma with FFP as a complement source could fully restore full complement functionality. This study describes for the first time a combined heterozygous genetic variation in complement C2 and C8B which, however, cannot fully explain the overall dysfunctions and calls for further complement deficiency research and corresponding therapies.